Short Note: Traverse Computation on the Ellipsoid Instead of on the Map Plane - Featherstone, Will; Kirby, Jonathan (The Institution of Surveyors, Australia Inc., 2002)
This short note describes an approach to compute coordinates from a survey traverse (properly reduced to the spheroid) without the need for tedious iterative computations via the map grid. A numerical example of a ~160km traverse is used to illustrate the efficiency and accuracy of the proposed approach. This shows a 67% improvement in efficiency, and the final coordinates agree to within 2mm ineasting and 3mm in northing with those computed using the map-grid-based approach.